Variação na composição proteica dos grãos de sorgo, em função da adubação nitrogenada e fosfatada e das épocas de plantio - C de Azevedo, Mauricio Wagner; Nogueira Fontes, Luiz Antônio; de Almeida Filho, José (Revista Ceres, 2025)
A study was conducted in Viçosa, Minas Gerais, to determine the effects of nitrogen and phosphorus fertilizers and planting dates on grain protein content and grain protein yield per hectare in grain sorghum (Sorghum bicolor (L.) Moench).